2015
DOI: 10.5539/ijef.v7n3p165
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Rental Rates and Selling Prices of Office Spaces in Jakarta: A Macroeconometric Model Using VECM Approach

Abstract: This paper empirically examines the macroeconomic factors that affect the rental rates and selling prices of office space. The data are in the form of quarterly time series which are used for the period of 1996: 1 to 2012: 4 period. In addition, quantitative methods in the form of Vector Error Correction Model (VECM) are also used in this study. The results showed that there is a long-term relationship between macroeconomic variables with the rental rate and selling prices of office space. IRF and FEVD showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…, 1998; Brennan et al. , 1984; Clapp, 1980a, b; Dunse and Jones, 1998; Slade, 2000; Fuerst, 2007; Öven and Pekdemir, 2004, 2006; Ozus, 2009; Simon et al. , 2015; Silva, 2016; Tomonidie, 2016; Bera and Uyar, 2019).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…, 1998; Brennan et al. , 1984; Clapp, 1980a, b; Dunse and Jones, 1998; Slade, 2000; Fuerst, 2007; Öven and Pekdemir, 2004, 2006; Ozus, 2009; Simon et al. , 2015; Silva, 2016; Tomonidie, 2016; Bera and Uyar, 2019).…”
Section: Related Literaturementioning
confidence: 99%
“…When reviewing various studies conducted over time, Pekdemir (2004, 2006) categorized determinants into four categories: econometric factors, building characteristics, locational features, and contract terms. Several studies conducted in diverse contexts have highlighted the influences of building characteristics and locational features on office rents (for example, Mills, 1992;Bollinger et al, 1998;Brennan et al, 1984;Clapp, 1980a, b;Dunse and Jones, 1998;Slade, 2000;Fuerst, 2007;Pekdemir, 2004, 2006;Ozus, 2009;Simon et al, 2015;Silva, 2016;Tomonidie, 2016;Bera and Uyar, 2019). In terms of quality, commercial office properties are commonly grouped into different classes, such as A, B, C and D (Nase et al, 2013), with Class A being considered the best, and class D the least desirable (Glascock et al, 1990).…”
Section: Related Literaturementioning
confidence: 99%
“…Generally, variables affecting real estate are divided into micro variables synonymous with supply factors and macroeconomic variables synonymous with demand factors (Zawir Simon et al. , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In modelling real estate price generally, many researchers have verified micro variables and hence, physical features of office buildings, as the defining variable in their rent cum price determination (Öven and Pekdemir, 2006a); thus, it is a fundamental price determination criteria (Chiarazzo et al. , 2014; Zawir Simon et al. , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using office market data from Jakarta spanning from 1996 to 2012 Simon, Achsani, Manurung, and Sembel explored relations between rents and several macroeconomic variables. Using the VECM model they found that rental rates responded to services sector employment, exchange rate and economic growth (Simon et al, 2015). Interesting empirical evidence on the nature of rent determinants and rent adjustments comes from office markets in Hong Kong (Chau & Wong, 2016) and Singapore (Ho et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%